Workplace Harassment and Intention to Leave in Nepalese Organisations: A Mediating Role of Psychological Stress - Malla, Shreya; Tamang, Puja (Journal of Business and Social Sciences Research, 2023)
This study aims to analyse the impact of workplace harassment on intention to leave where psychological stress as mediator was used to examine its intensity on the relationship between workplace harassment and intention to leave. Convenience and snowball sampling technique was adopted to select the employees working in different sectors situated within the Kathmandu Valley. Regression Analysis from Hayes macro process was conducted from the responses of 199 respondents to generate the results of mediation effect. The findings indicate that workplace harassment has a positive significant impact on employee’s intention to leave. In addition, it was found that the psychological stress mediates the relationship between workplace harassment and intention to leave. Future studies can be conducted through qualitative methods among the employees of different sectors or specific industries for indepth analysis of the harassment and its consequences the employees are facing.